STRATEGI MEMBANGUN PERSONAL BRANDING DALAM MENINGKATKAN PERFORMANCE DIRI - DHARMA SETIAWAN (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
Marketing a products needs an effective marketing strategy, with the aim that in addition to being able to meet the needs and wants of target consumers, also get positioning as well as reaching a broad market-share. Personally, everyone needs to